Efektifitas Media Booklet Terhadap Pengetahuan Jenis Tumbuhan Paku Pada Mahasiswa Program Studi Pendidikan Biologi: (The Effectiveness of Booklet Media on Knowledge Types of Ferns in Students Biology Education Study Program) - Muswita Muswita; Upik Yelianti; Pinta Murni (BIODIK, 2021)
One of the obstacles faced by students in studying plant taxonomy is the difficulty of recognizing various types of ferns. The purpose of the study was to develop a media booklet on knowledge of fern species in Biology Education study program students. The research method is a quasi experimental design (Pretest-Posttest Control Group Design). The instrument is a written test sheet in the form of multiple choice. The pretest and posttest data were analyzed using SPSS using the paired sample t-test, then continued with the independent sample t-test. Test data independent sample t test obtained Sig. (2-tailed) of 0.000 < 0.05. N-Gain Score, shows the average value of N for the experimental class is 69.79 which is included in the "fairly effective" category. With a minimum N-gain score of 50% and a maximum of 87%. While the average value of the N-gain score in the control class is 55.05% which is included in the "less effective" category. With a minimum N-gain score of 33% and a maximum of 75%. The conclusion is that the use of booklets is more effective in learning to increase students' knowledge of the introduction of fern species. Abstrak. Salah satu kendala yang dihadapi mahasiswa dalam pempelajaran taksonomi tumbuhan adala Â kesulitanÂ Â  mengenal berbagai jenis tumbuhan paku. Â Â Tujuan penelitian adalah mengembangkan Media booklet terhadap pengetahuanÂ  jenis tumbuhan paku pada mahasiswa program studi Pendidikan Biologi. Metode penelitian adalah quasi experimental design (Pretest-Posttest Control Group Design). Instrumen berupa lembar tes tertulis berbentuk pilihan ganda. Data pretest danÂ  posttestÂ  dianalisis Â menggunakan SPSS dengan menggunakan uji paired sample t-test, kemudian dilanjutkan dengan uji independent sample t-test. Data Uji independent sample t test diperoleh Sig. (2-tailed) sebesar 0,000 < 0,05. N-Gain Score, menunjukkanÂ  nilai rata-rata N untuk kelas eksperimen adalah Â 69,79 termasuk dalam kategori â€œcukup efektifâ€. Dengan nilai N-gain score minimal 50% dan maksimal 87%. Sedangkan nilai rata-rata N-gain score pada kelas kontrol adalah sebesar 55,05% termasuk dalam kategori â€œkurang efektifâ€. Dengan nilai N-gain score minimal 33% dan Â maksimal 75%. Â Simpulannya Â adalah penggunaan Â booklet lebih efektif digunakan dalam pembelajaran untuk meningkatkan pengetahuan mahasiswa terhadap pengenalan Â jenis tumbuhan paku. Â